2008
DOI: 10.1016/j.breast.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breast lesions with contrast-enhanced ultrasound using the microvascular imaging technique: Initial observations

Abstract: The objective of this study was to evaluate the usefulness of contrast-enhanced ultrasound using the microvascular imaging technique in the diagnosis of breast lesions. In 104 patients with 104 breast lesions scheduled for surgery, conventional and contrast-enhanced ultrasound using the microvascular imaging technique were performed after administration of SonoVue. The enhancement patterns of breast lesions were classified as no enhancement, peripheral enhancement, homogeneous enhancement, regional enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 16 publications
3
64
1
Order By: Relevance
“…Breast lumps in prepubertal and adolescent girls can be imaged using the modalities of ultrasound, computed tomography, and magnetic resonance imaging. Thermography has been used to differentiate phyllodes from fibroadenoma [27], but more recently, the use of contrast-enhanced ultrasound with its ability to image the microvascular characteristics of breast lesions has shown encouraging results in the differentiation of these lesions [28,29]. Management of phyllodes tumor remains controversial, and the decision of how to treat this condition in younger patients can be even more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast lumps in prepubertal and adolescent girls can be imaged using the modalities of ultrasound, computed tomography, and magnetic resonance imaging. Thermography has been used to differentiate phyllodes from fibroadenoma [27], but more recently, the use of contrast-enhanced ultrasound with its ability to image the microvascular characteristics of breast lesions has shown encouraging results in the differentiation of these lesions [28,29]. Management of phyllodes tumor remains controversial, and the decision of how to treat this condition in younger patients can be even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Management of phyllodes tumor remains controversial, and the decision of how to treat this condition in younger patients can be even more challenging. Spread is rare and usually hematogenous, primarily to the lungs, and there are anecdotal successes with adjuvant and palliative therapy [3,[20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [34] evaluated the usefulness of CEUS using the microvascular imaging technique in the diagnosis of breast lesions. The authors found that nonenhancement was suggestive of benignity, with a sensitivity of 18.3%, specificity of 97.7%, positive predictive value of 91.7%, negative predictive value of 46.2%, and accuracy of 51.5%.…”
Section: Gallbladdermentioning
confidence: 99%
“…(15) andZhao et al (16) used 2.4 mL dose of MB as a bolus to differentiate benign from malignant lesions in the breast. The same dose of 2.4 mL of contrast agent was used by Wang et al (17) in the study of different histopathological types of breast cancers.…”
mentioning
confidence: 99%